Implementation of Digital Governance in One-Stop Integrated Licensing Services: A Case Study of the SAMIRINDU-PASTI BEDAS Application in Bandung Regency - Putra, Raenaldi Ramanda; Ariesmansyah, Andre (Ilomata International Journal of Social Science, 2024)
This study aims to explain the running of digital governance in one-stop integrated services carried out at the Bandung Regency Investment and One-Stop Integrated Services Office (DPMPTSP) which has been running since the issuance of Regional Regulation Number 15 of 2018 concerning Amendments to Regional Regulation Number 12 of 2016 concerning the Formation and Composition of Regional Apparatus. The research method used in this study is a descriptive research method with a qualitative approach. where the researcher describes the facts about the problem that is the focus and is ringed with accurate interpretation through in-depth interviews. The digital governance model used in this study is the Welchaman Model (2015). The results of this study show that the Bandung Regency Government, through the One-Stop Investment and Integrated Services Office (DPMPTSP), implements an electronic licensing system through the SAMIRINDU - PASTI BEDAS application with the aim of simplifying the licensing process and improving the accessibility of services for the community. This application allows applicants to apply for permits online and print their permits through the application once approved. The digital governance of one-stop integrated services in Bandung Regency has been implemented quite well, but there are several disruptions to the server and a lack of understanding of licensing procedures are obstacles. So that the goal of integrated services, namely fast and precise, has not been achieved optimally.